An Ideal Model of Procedural Law in The Religious Courts For Resolving Muslim Family Disputes in The Digital Era - Waluyo Sudarmaji; Muhlil Musolin; Muhajir Muhajir (QONUN: Jurnal Hukum Islam dan Perundang-undangan, 2025)
The digital transformation of the judicial system has significantly influenced procedural law in the Religious Courts, particularly in resolving Muslim family disputes. This study aims to analyze the implementation of digital-based procedural law, identify normative, technical, and sociological challenges, and formulate an ideal model of procedural law for Religious Courts in the digital era. This research employs a library research method with a qualitative approach by examining statutory regulations, scholarly literature, and previous studies. The findings indicate that digitalization through e-court and e-litigation systems developed by Mahkamah Agung Republik Indonesia has improved efficiency and accessibility of judicial services; however, it has not fully addressed the complexity of Muslim family disputes. The main challenges include regulatory limitations, technological infrastructure constraints, and low levels of digital literacy among the public. Based on the analysis of legal system theory, access to justice, and maqÄá¹£id al-sharÄ«”˜ah, this study proposes an integrative ideal model of procedural law through a hybrid approach, strengthened digital evidence regulation, optimization of value-based mediation, and inclusive access to justice. This model is expected to establish a judicial system that is not only procedurally efficient but also substantively just in resolving Muslim family disputes.